Pengaruh Electronic Word of Mouth Terhadap Keputusan Pembelian Produk: Studi Regresi pada Skintific di Media Sosial Tiktok Pada Generasi Z - Labora, Anju (Brand Communication, 2025)
The development of digital technology has had a significant impact on finding information, as people can easily access information through social media. Tiktok is one of the popular social media platforms among generation Z so companies or brands compete to use Tiktok as their marketing media. One of the brands in the beauty sector, namely Skintific, is a beauty brand that actively promotes its products on TikTok. This study aims to determine the influence of Electronic Word of Mouth on Purchasing Decisions for Skintific products on TikTok among Generation Z. The method used in this study is a quantitative method. Data collection is obtained from an online questionnaire (google form) using a purposive sampling method with a sample size of 100 respondents. Based on the data analysis, the results of the study obtained a relationship between variable X (electronic word of mouth) and variable Y (purchase decision) of 0.803. The results of this study indicate that there is an influence between electronic word of mouth and the decision to purchase Skintific products on Tiktok among generation Z of 80.3%. From the results of this study, it is hoped that brands can increase positive e-WOM in order to build the trust of generation Z to make purchasing decisions.